2012
DOI: 10.1155/2012/741545
|View full text |Cite
|
Sign up to set email alerts
|

Regular Physical Exercise as a Strategy to Improve Antioxidant and Anti-Inflammatory Status: Benefits in Type 2 Diabetes Mellitus

Abstract: Over the last 30 years the combination of both a sedentary lifestyle and excessive food availability has led to a significant increase in the prevalence of obesity and aggravation of rates of metabolic syndrome and type 2 diabetes mellitus (T2DM). Several lines of scientific evidence have been demonstrating that a low level of physical activity and decreased daily energy expenditure leads to the accumulation of visceral fat and, consequently, the activation of the oxidative stress/inflammation cascade, which u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 155 publications
2
51
0
6
Order By: Relevance
“…The present study showed that Celastrol promoted mitochondrial biogenesis and inhibited mitochondrial ROS production. Chronic inflammatory cytokines are also potent stimulators of ROS production, and ROS can induce oxidative stress, with the subsequent activation of inflammatory pathways and mitochondrial damage [31], [32], [33]. Previous studies have shown that Sirt1 has a regulatory effect on oxidative stress in many tissues through reducing the ROS levels and improving cell survival via this antioxidant effect [34].…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that Celastrol promoted mitochondrial biogenesis and inhibited mitochondrial ROS production. Chronic inflammatory cytokines are also potent stimulators of ROS production, and ROS can induce oxidative stress, with the subsequent activation of inflammatory pathways and mitochondrial damage [31], [32], [33]. Previous studies have shown that Sirt1 has a regulatory effect on oxidative stress in many tissues through reducing the ROS levels and improving cell survival via this antioxidant effect [34].…”
Section: Discussionmentioning
confidence: 99%
“…Increased physical activity and weight loss are associated with lower CRP and reduction in concentration of other markers of inflammation3392. Therefore, both intervention alone or in combination might act through AMPK pathway and inhibit the activation of downstream inflammation through inhibition of CRP and NFκB.…”
Section: Discussionmentioning
confidence: 99%
“…Regular exercising affects the regulation of enzymatic antioxidants such as catalase, super oxide dismutase and non-enzymatic antioxidants including vitamin E and C. Regular exercise is linked to CRP reduction, lipid profile regulation, increase of nitric oxide synthase, improvement in insulin sensitivity, and preservation of beta cell mass. Thus regular exercise leads to the adaptation in antioxidant capacity, protecting cells against harmful effects of oxidative stress33.…”
mentioning
confidence: 99%
“…Although a vast amount of research has been conducted to understand the mechanism by which exercise alters the development of obesity and T2D, its effects on glucose-induced insulin secretion by β-cells is poorly understood. In terms of pancreatic function, experiments in humans and animals have variously demonstrated that exercise improves insulin resistance, increases insulin sensitivity, increases pancreatic β-cell mass and generally enhances β-cell function and insulinotropic action, especially in T2D patients [6]. However, the glucose responsiveness of the pancreatic islets obtained from trained rats varies according to the protocol (acute or chronic exercise), glucose concentration and metabolic state (diabetic, obese or lean rats).…”
Section: Introductionmentioning
confidence: 99%